The power of self-leadership! Unravelling the role of self-leadership on academics’ research productivity - Sinyati Ndiango (Cogent Education)
Self-leadership has been recognized as a factor influencing work outcomes in various job settings. However, its impact on research productivity in universities remains relatively unexplored. Therefore, this study investigates the impact of self-leadership on research productivity in universities, as well as the mediating role of research self-efficacy and the moderating role of gender. Data were gathered from 212 academics in two public universities in Tanzania using structured questionnaires and were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The sample size was obtained using Yamane formula. The findings indicate that self-leadership contributes significantly to explaining research productivity, and that research self-efficacy partially mediates this relationship. This provides a clear understanding on how self-leadership enhances research self-efficacy which in turn leads to improved academics’ research productivity. These findings emphasize the importance of self-leadership in bolstering academics’ confidence in conducting research, leading to heightened research output.